Power-S Approach to Solve Problems of Students` Academic Writing - Rasulova Sohiba Azizjonovna; Tursunova Yosuman Ravshanzoda (European Science Publishing, 2023)
This article deals with the issue that students who face difficulties on academic writing and also teachers can use because it investigates latest approaches and techniques for solving student`s writing problems throw these ways.
Keywords: POWER-S technique, writing skill, academic writing, English as Second language